Banking the unbanked : the journey of Indian Bank - Barua, S. K. (Samir K.); Agarwalla, Sobhesh Kumar (London : Indian Institute of Management, Ahmedabad, 2015)
In emerging economies like India, in addition to commercial banking, Public Sector Banks (PSBs), with majority shareholding by the government, are often required to pursue developmental/social objectives such as that of financial inclusion. The case describes the strategy framed and executed by Indian Bank, a large PSB in India, to enhance financial inclusion in its area of operation. Given the relatively low level of literacy in India, the Bank had to devise processes that were agnostic to the level of education of people covered by its initiatives. In addition, India being a vast country, the Bank had to devise ways of serving areas that were not easily accessible. The challenge that the Bank faced was that while pursuing the developmental objective which was 'imposed' on the PSBs by the Central Bank of the country - the Reserve Bank of India (RBI), with concurrence of the government, it had to be mindful of the costs associated with the initiatives. As a listed entity, it had to be concerned with protecting the interests of its minority shareholders. Activities that were clearly not profitable, though concurred to by the dominant shareholder (the government), could not be justified from the point of view of the other shareholders. The case provides details of the strategic response of Indian Bank to the requirement imposed by public policy.
Originally Published InBarua, S. K., & Agarwalla, S. K. (2015). Banking the unbanked: The journey of Indian Bank. Ahmedabad, IN: Indian Institute of Management, Ahmedabad.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Indian Bank -- Management; Indian Bank -- Marketing; Reserve Bank of India; Bank marketing -- India -- Case studies; Bank marketing -- Law and legislation -- India; Banks and banking -- India -- Information services -- Case studies; Bank management -- India -- Case studies